2021
DOI: 10.1093/plphys/kiab008
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid homeostasis is critical for the functionality of the Medicago truncatula pulvinus

Abstract: Many plant species open their leaves during the daytime and close them at night as if sleeping. This leaf movement is known as nyctinasty, a unique and intriguing phenomenon that been of great interest to scientists for centuries. Nyctinastic leaf movement occurs widely in leguminous plants, and is generated by a specialized motor organ, the pulvinus. Although a key determinant of pulvinus development, PETIOLULE-LIKE PULVINUS (PLP), has been identified, the molecular genetic basis for pulvinus function is larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Interestingly, a recent study showed that the geometry of the compound leaf is important for leaf movement in Medicago truncatula [ 67 ]. Moreover, the plant hormone BR homeostasis is critical for nyctinastic leaf movement but has no effect on pulvinus determination [ 68 ]. In this study, the KEGG pathway enrichment analysis showed that the DEGs were highly enriched in BR biosynthesis ( Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study showed that the geometry of the compound leaf is important for leaf movement in Medicago truncatula [ 67 ]. Moreover, the plant hormone BR homeostasis is critical for nyctinastic leaf movement but has no effect on pulvinus determination [ 68 ]. In this study, the KEGG pathway enrichment analysis showed that the DEGs were highly enriched in BR biosynthesis ( Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Brassinosteroids are also becoming known as regulators of pulvinar development downstream of the ELP1/PLP pathway. Kong et al found that overexpression of ELP1/PLP activated the expression of BAS1, an inhibitor of brassinosteroid biosynthesis, indicating that the brassinosteroid signaling pathway played a role downstream of ELP1/PLP [ 23 ]. Through forward genetics, Zhao et al obtained a nyctinastic movement-deficient mutant of M. truncatula , mtdwf4 [ 24 ].…”
Section: Molecular Genetic Studies Of the Pulvinusmentioning
confidence: 99%
“…Brassinosteroids Insensitive 1 ( BRI1 ) is required for BR perception and initiation of subsequent signal transduction in Arabidopsis ( Li and Chory, 1997 ). In Medicago, the loss-of-function mutant of MtBRI1 has typical BR-deficient phenotypes of extreme dwarfness and infertility, and its leaves were thickened, curled, dark green, and greatly reduced in size with the petioles and rachises failed to elongate ( Cheng et al, 2017 ; Kong et al, 2021 ). MtDWARF4A ( MtDWF4A ), a gene encoding a cytochrome P450 protein orthologous to A. thaliana DWARF4, is required for the BR biosynthesis.…”
Section: The Genetic Control Of Leaf Organ Size and Marginal Serrationsmentioning
confidence: 99%
“…MtDWARF4A ( MtDWF4A ), a gene encoding a cytochrome P450 protein orthologous to A. thaliana DWARF4, is required for the BR biosynthesis. The mtdwf4a mutant exhibits mild BR-deficient phenotypes, semi-dwarfism, short petioles, and rachis, but normal fertility ( Kong et al, 2021 ; Zhao et al, 2021 ). The MtDWF4A has a highly homologous copy designated as MtDWF4B , it will be critical to explore the possibilities of functional redundancy and diversification between MtDWF4A and MtDWF4B in the BR biosynthetic pathways ( Zhao et al, 2021 ).…”
Section: The Genetic Control Of Leaf Organ Size and Marginal Serrationsmentioning
confidence: 99%